Multianalyte Conventional Reference Material (MacRM): A Useful Tool for Nationwide Standardization of Laboratory Measurements for Medical Care—A Model Study in Japan. (6th January 2020) - Shinohara, Katsuyuki; Hamasaki, Naotaka; Takagi, Yasushi; Yatomi, Yutaka; Kikuchi, Hiroshi; Hosogaya, Shigemi; Kawai, Yohko; Miyachi, Hayato; Kaneko, Kenji; Miyajima, Yoshifumi; Matsumoto, Hiroyuki; Yamamoto, Yoshikazu; et al.
Abstract: BACKGROUND: The Japanese Committee for Clinical Laboratory Standards (JCCLS) has developed a multianalyte conventional reference material (MacRM) for nationwide standardization of laboratory measurements. METHODS: To prepare the MacRM, pooled sera were obtained from healthy Japanese individuals. Target values of the pooled sera for 30 analytes were assigned on the basis of the measurement results of 45 certified clinical laboratories whose calibration was verified by measuring certified reference materials (CRMs) provided by the National Institute of Standards and Technology, the Institute for Reference Materials and Measurements, and JCCLS. Commutability of MacRM was assessed by comparison with results for 150 individual inpatients at Fukuoka University Chikushi Hospital. Survey samples were prepared by essentially the same method for MacRM but without target values. The survey samples were used to assess agreement among 165 laboratories that used various assay kits and platforms calibrated with the MacRM. RESULTS: The commutability of MacRM was confirmed for 30 analytes with sera from 150 individual patients. The imprecision (CV) of measurements of survey samples (high and low concentrations) among the 165 laboratories was 0.4%–10.0%. Twenty-six of 30 analytes were within the goals for interinstitutional allowable bias. An aliquot of MacRM stored frozen at −80 °C remained stable for ≥4 years. CONCLUSIONS: The MacRM was successfully applied as a calibrator to achieve nationwide standardization for 30 analytes measured by 165 laboratories that used various methods from different manufacturers.